Evaluasi Kualitas Sensoris Muffin Berbahan Baku Pisang Goroho (Musa acuminate sp.) - Fiqih V. Albanjar; Erni Nurali; Lana Lalujan; Tineke Langi (Universitas Sam Ratulangi, 2014)
ABSTRACTGoroho plantain (Musa acuminate sp.) is a kind of local endemic food from North Sulawesi. As a carbohydrate source, goroho plantain was mostly consumed by people in that area. Many efforts have been done to promote the composite flour, recently. Substitution of goroho flour to make a various food products such as muffin is one of that attempt. This research was aimed to evaluate the sensoric quality of muffin made from goroho flour. The statistical analysis of this research was Complete Random Design (CRD) where substitution of goroho flour was the treatment. The result of ANOVA showed that substitution of goroho flour were not affected the quality sensoric of muffin in color, smell, flavor and texture of muffin. The organoleptic test of muffin was give the result that substituted by 100 % goroho flour give the most preferred in color (3,84) and flavor (3,80). But the most preferred smell (3,88) of muffin was substituted by 50% goroho flour and the most preferred texture (3,76) of muffin was substituted by 75% goroho flour.Keywords : Goroho Plantain, Muffin.